STRES DALAM SENI LUKIS EKSPRESIONIS - Drs. Abd. Hafiz, M.Pd., RIDHO KEMALDI, Yasrul Sami, S.Sn., M.Sn., (Jurusan Seni Rupa FBS UNP Padang, 2018)
This art work aim is to visualised stress dissorder, The factors, the characteristics, the steps, and how to overcome. The method of this activity was preparation,Â laboration, synthesis, realisation concept, finishing touch, and show at exhibitions. Using acrylic paint as a main element on canvas in ekspresionism style. This art work activity is giving the basic knowledge about stress to the public as an anxiety because of personal problem and in many cases, are ignored, as ten art works in expressionism style: Terbang Terkunci, Cengkraman Gaduh, Phobia, Depresi, Bipolar, Obsessive, Hysteria, Coping, Balance, Survive.Kata Kunci: Stres, Seni Lukis, Ekspresionis